Direct vascular actions of quercetin in aorta from renal hypertensive rats - Choi, Seok; Ryu, Kwon Ho; Park, Sang Hag; Jun, Jae Yeoul; Shin, Byung Chul; Chung, Jong Hoon; Yeum, Cheol Ho (Kidney research and clinical practice, 2016)
Abstract Background Chronic treatment with the dietary flavonoid quercetin is known to lower blood pressure and restores endothelial dysfunction in animal models of hypertension. This study investigated the direct effects of quercetin on vascular response in chronic two-kidney, one clip (2K1C) renal hypertensive rats. The effects of antioxidant vitamin ascorbic acid on the vasoreactivity were also examined. Methods 2K1C renal hypertension was induced by clipping the left renal artery; age-matched rats received sham treatment served as controls. Thoracic aortae were mounted in tissue baths for the measurement of isometric tension. Results Relaxant responses to acetylcholine were significantly attenuated in 2K1C rats in comparison with sham rats. Quercetin or ascorbic acid augmented acetylcholine-induced relaxation in 2K1C rats, while no significant differences were noted in sham rats. The relaxation response to sodium nitroprusside (SNP) was comparable between 2K1C and sham rats and SNP-induced relaxation was not altered by quercetin or ascorbic acid in either group. The contractile response to phenylephrine was significantly enhanced in 2K1C rats compared to sham rats. Phenylephrine-induced contraction was inhibited by pretreatment with quercetin or ascorbic acid in 2K1C rats, while neither chemical affected responses in sham rats. Nw-nitro-L-arginine methyl ester (L-NAME) markedly augmented the contractile response to phenylephrine in sham rats, while no significant differences were observed in 2K1C rats. Quercetin or ascorbic acid did not affect phenylephrine-induced contraction in the presence of L-NAME in either 2K1C or sham rats. Conclusion Acute exposure to quercetin appears to improve endothelium-dependent relaxation and inhibit the contractile response, similar to the effect of ascorbic acid in 2K1C hypertension. These results partially explain the vascular beneficial effects of quercetin in renal hypertension.